No Taxation Without Representation In Local Policy: Ensuring Public Participation In Indonesia’s Rural And Urban Land And Building Tax Formulation - Bibianus Hengky Widhi Antoro; Jery Satria Bagas Putra; Yupita Jevanska Atuna (Universitas Lampung, 2026)
Fiscal decentralization through Regional Taxes, such as the Rural and Urban Land and Building Tax (PBB-P2), has led to unresolved issues, including sharp increases in tax amounts based on Head of Region Regulations. Broad authority over Tax Object Sale Value (NJOP) combined with limited public participation conflicts with the principle of “No Taxation Without Representation,” generating social unrest and questioning legal legitimacy. This study employs normative legal research using statutory, case, and comparative approaches. It finds that Constitutional Court-mandated rights to be heard, considered, and explained have not been implemented. Effective PBB-P2 regulation requires proactive transparency and deliberative forums during planning, drafting, and deliberation stages, drawing on German best practices to strengthen legitimacy and social stability.